Neurological speech therapy for toddlers with vocal cord paralysis – a holistic approach: case studies - Knapek, Magdalena; Wójcik-Topór, Paulina (Logopedia Silesiana, 2022)
The theoretical aspect of the article presents dysphagia and dysphonia in children with vocal fold paralysis caused by surgical interventions – the causes, symptoms, diagnostic possibilities, as well as initial therapeutic recommendations. In practical terms, the authors would like to show methods of examining the voice and swallowing disorders in toddler patients who participated in the experimental-clinical trial at the University Children’s Hospital in Krakow. The article discusses two case studies which were to be used to develop a standard of neurological therapy dedicated to this type of patients. The authors focused on presenting the relationship between the functional/ myofunctional diagnosis, and the diagnosis of the prelingual and linguistic skills in children in terms of the development of linguistic and communicative competence. In this approach, myotherapy is to form the basis of activities necessary in the framework of early therapeutic intervention, which are to stimulate the speech development in children. In conclusion, the article specifies the therapeutic recommendations that have been developed on the basis of the research procedures presented.